Pelatihan Teknis Pembuatan Laporan Keuangan Berbasis SIAPIK Bagi Pelaku UMKM Kuliner Pemula di Kota Jayapura - Erari, Anita; Attamimi , Yasir; Kuddy , Aprianto L.; Ahlia, Isma S.; Sitompul, Fanny K.T.; Setiarini , Neni; Mangopo, Yuni Riskita (Cenderabakti: Jurnal Pengabdian Kepada Masyarakat, 2025)
The implementation of Technical Training for Making Financial Reports Based on the SIAPIK Financial Information Recording Application System for UMKM Beginner Culinary in Jayapura City, this training to improve the skills and knowledge of culinary business actors in more professional and systematic financial management. This training was attended by 24 participants who are culinary business actors, who are beginners. Through this training, they can have basic knowledge of simple accounting principles and practical use of applications as a form of recording their financial information. This training is carried out through an operational and practical approach and is technology-based, namely with materials in the form of an introduction to the basic functions of the SIAPIK application, as well as direct practice in operating it. The achievements obtained through this training are that participants become aware of making financial records in accordance with accounting standards. Participants also have accounts in the SIAPIK application system. Thus, what has been obtained through this training is a supporting factor for the development of UMKM owned by participants.